Pengaruh Literasi Keuangan, Sikap Keuangan Dan Gaya Hidup Pada Perilaku Keuangan Generasi Milenial - Pratama, Dimas Yogi; Kusumawardhani, Ratih; Maulida, Alfiatul (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This research aims to determine the influence of financial literacy, financial attitudes and lifestyle on the financial behavior of the millennial generation. And to find out whether these variables influence each other. The method used in this research is quantitative with 101 respondents. Data was collected via a Google form which was distributed online and processed using SPSS 2.0. The findings found that financial literacy had no significant effect on financial behavior. Financial attitudes have a significant influence on financial behavior in the millennial generation. Meanwhile, lifestyle has a significant influence on financial behavior in the millennial generation. This research provides information regarding the influence of financial literacy, financial attitudes and lifestyle on financial behavior which is very useful and can be used as an input regarding financial behavior in the millennial generation.